If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(3x + -2) + -1x + -3 = -4(4x + 5) + 13 Reorder the terms: 5 + -1(-2 + 3x) + -1x + -3 = -4(4x + 5) + 13 5 + (-2 * -1 + 3x * -1) + -1x + -3 = -4(4x + 5) + 13 5 + (2 + -3x) + -1x + -3 = -4(4x + 5) + 13 Reorder the terms: 5 + 2 + -3 + -3x + -1x = -4(4x + 5) + 13 Combine like terms: 5 + 2 = 7 7 + -3 + -3x + -1x = -4(4x + 5) + 13 Combine like terms: 7 + -3 = 4 4 + -3x + -1x = -4(4x + 5) + 13 Combine like terms: -3x + -1x = -4x 4 + -4x = -4(4x + 5) + 13 Reorder the terms: 4 + -4x = -4(5 + 4x) + 13 4 + -4x = (5 * -4 + 4x * -4) + 13 4 + -4x = (-20 + -16x) + 13 Reorder the terms: 4 + -4x = -20 + 13 + -16x Combine like terms: -20 + 13 = -7 4 + -4x = -7 + -16x Solving 4 + -4x = -7 + -16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16x' to each side of the equation. 4 + -4x + 16x = -7 + -16x + 16x Combine like terms: -4x + 16x = 12x 4 + 12x = -7 + -16x + 16x Combine like terms: -16x + 16x = 0 4 + 12x = -7 + 0 4 + 12x = -7 Add '-4' to each side of the equation. 4 + -4 + 12x = -7 + -4 Combine like terms: 4 + -4 = 0 0 + 12x = -7 + -4 12x = -7 + -4 Combine like terms: -7 + -4 = -11 12x = -11 Divide each side by '12'. x = -0.9166666667 Simplifying x = -0.9166666667
| 26=j-24 | | 48-19-29-51= | | 17+840=22x+760 | | 3x+(-7)=8x | | 6x-2=6(x+4) | | 14=w/2-11 | | x=-2.5x | | n-17=-17 | | 6y+12=-2-4 | | 71x+-1+20x+90=180 | | 50=f-8 | | 2(x+10)-x+11=13 | | -x+4+2x=5-2(x-1) | | -b-2b-3b+4=-64 | | .375(x+.25)-1.50=x-.3333 | | -10-4p=20 | | 10x+3+5x-16=180 | | c-11=35 | | 100=5/6x | | 5x3/05 | | 10x+3+5-16=180 | | -348=6(-5x-8) | | -1+h=-5 | | 41.25=3(t+5.50) | | 2^2y^-6/8^-1z^0x^-7 | | .625(x+.25)-1.50=x-.33 | | Y=3x^2+5x+-1 | | 0.50x+0.35=29.5 | | 290+33+x=360 | | 3(x-2y)+5x= | | 5(x+4)-4x=10 | | x+2(-0.2x-0.2)=13 |